ANALISIS KOMPARATIF IMPELEMNTASI PROGRAM TOTAL QUALITY MANAGEMENT (TQM) DAN KEPUASAN PASIEN RAWAT INAP DAN RAWAT JALAN (STUDI KASUS PADA RUMAH SAKIT BINA KASIH DAN RUMAH SAKIT LANCANG KUNING) - Pardede, Jackson Paulus; Indarti, Sri; Daulay, Iwan Nauli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to find out the Program Implementation Differences Total Quality Management (TQM) applied by each hospital, and Satisfaction Inpatient and Outpatient. The population in this study all employees and all inpatients and outpatients. The dependent variable in this study is Total Quality Management (TQM), while the independent variable is Satisfaction of Inpatient and Outpatient. For the determination of the sample using the formula slovin research. This study used two sampling techniques. First to determine the number of samples Inpatient using accidental sampling technique, while to determine the number of samples Employees and Outpatient with Purposive Random Sampling technique. Methods of data processing using comparative analysis, one way ANOVA test (ANOVA test), and t-test. 21:00 SPSS software version. The results showed that there are differences in Program Implementation of Total Quality Management (TQM) and there is a significant difference between satisfaction Inpatient and Outpatient Patient Satisfaction at Bina Kasih Hospital and the Hospital of Lancang Kuning.Keywords: Total Quality Management (TQM), Satisfaction Inpatient and Outpatient Patient Satisfaction